CETP Inhibitor Evacetrapib Reduces LDL-C and Raises HDL-C Levels - Buckley, Rita (MD Conference Express, 2011)
Results from a Phase 2 randomized controlled trial of the novel cholesteryl ester transfer protein (CETP) inhibitor evacetrapib are discussed. Compared with placebo or statin monotherapy, evacetrapib with or without a statin increased high-density lipoprotein cholesterol (HDL-C) and decreased low-density lipoprotein cholesterol (LDL-C) levels in patients with dyslipidemia [Effects of the CETP Inhibitor Evacetrapib Administered as Monotherapy or with Statins on HDL and LDL Cholesterol Trial; NCT01105975].